Putative Ancestral Origins of Chromosomal Segments in Individual African Americans: Implications for Admixture Mapping - Seldin, Michael F.; Morii, Takanobu; Collins-Schramm, Heather E.; Chima, Bill; Kittles, Rick; Criswell, Lindsey A.; Li, Hongzhe (Genome Research, 2004)
Theoretically, markers that distinguish European from West African ancestry can be used to examine the origin of chromosomal segments in individual African Americans. In this study, putative ancestral origin was examined by using haplotypes estimated from genotyping 268 African Americans for 29 ancestry informative markers spaced over a 60-cM segment of chromosome 5. Analyses using a Bayesian algorithm (STRUCTURE) provided evidence that blocks of individual chromosomes derive from one or the other parental population. In addition, modeling studies were performed by using hidden real marker data to simulate patient and control populations under different genotypic risk ratios. Ancestry analysis showed significant results for a genotypic risk ratio of 2.5 in the African American population for modeled susceptibility genes derived from either putative parental population. These studies suggest that admixture mapping in the African American population can provide a powerful approach to defining genetic factors for some disease phenotypes.